An Imperial Homeland : Forging German Identity in Southwest Africa - Blackler, Adam A. (Book collections on Project MUSE., 2022)
At the turn of the twentieth century, depictions of the colonized world were prevalent throughout the German metropole. Tobacco advertisements catered to the erotic gaze of imperial enthusiasts with images of Ovaherero girls, and youth magazines allowed children to escape into "exotic domains" where their imaginations could wander freely. While racist beliefs framed such narratives, the abundance of colonial imaginaries nevertheless compelled German citizens and settlers to contemplate the world beyond Europe as a part of their daily lives.An Imperial Homeland reorients our understanding of the relationship between imperial Germany and its empire in Southwest Africa (present-day Namibia). Colonialism had an especially significant effect on shared interpretations of the Heimat (home/homeland) ideal, a historically elusive perception that conveyed among Germans a sense of place through national peculiarities and local landmarks. Focusing on colonial encounters that took place between 1842 and 1915, Adam A. Blackler reveals how Africans confronted foreign rule and altered German national identity. As Blackler shows, once the façade of imperial fantasy gave way to colonial reality, German metropolitans and white settlers increasingly sought to fortify their presence in Africa using juridical and physical acts of violence, culminating in the first genocide of the twentieth century.Grounded in extensive archival research, An Imperial Homeland enriches our understanding of German identity, allowing us to see how a distant colony with diverse ecologies, peoples, and social dynamics grew into an extension of German memory and tradition. It will be of interest to German Studies scholars, particularly those interested in colonial Africa.